Differential regulatory T cell signature after recovery from mild COVID-19 - de Sousa Palmeira, Pedro Henrique; Peixoto, Rephany Fonseca; Csordas, Bárbara Guimarães; de Medeiros, Isac Almeida; de Azevedo, Fátima de Lourdes Assunção Araújo; Veras, Robson Cavalcante; Janebro, Daniele Idalino; Amaral, Ian P.G.; Keesen, Tatjana Souza Lima (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by a range of symptoms in which host immune response have been associated with disease progression. However, the putative role of regulatory T cells (Tregs) in determining COVID-19 outcomes has not been thoroughly investigated. Here, we compared peripheral Tregs between volunteers not previously infected with SARS-CoV-2 (healthy control [HC]) and volunteers who recovered from mild (Mild Recovered) and severe (Severe Recovered) COVID-19. Peripheral blood mononuclear cells (PBMC) were stimulated with SARS-CoV-2 synthetic peptides (Pool Spike CoV-2 and Pool CoV-2) or staphylococcal enterotoxin B (SEB). Results of a multicolor flow cytometric assay showed higher Treg frequency and expression of IL-10, IL-17, perforin, granzyme B, PD-1, and CD39/CD73 co-expression in Treg among the PBMC from the Mild Recovered group than in the Severe Recovered or HC groups for certain SARS-CoV-2 related stimulus. Moreover, Mild Recovered unstimulated samples presented a higher Tregs frequency and expression of IL-10 and granzyme B than did that of HC. Compared with Pool CoV-2 stimuli, Pool Spike CoV-2 reduced IL-10 expression and improved PD-1 expression in Tregs from volunteers in the Mild Recovered group. Interestingly, Pool Spike CoV-2 elicited a decrease in Treg IL-17+ frequency in the Severe Recovered group. In HC, the expression of latency-associated peptide (LAP) and cytotoxic granule co-expression by Tregs was higher in Pool CoV-2 stimulated samples. While Pool Spike CoV-2 stimulation reduced the frequency of IL-10+ and CTLA-4+ Tregs in PBMC from volunteers in the Mild Recovered group who had not experienced certain symptoms, higher levels of perforin and perforin+granzyme B+ co-expression by Tregs were found in the Mild Recovered group in volunteers who had experienced dyspnea. Finally, we found differential expression of CD39 and CD73 among volunteers in the Mild Recovered group between those who had and had not experienced musculoskeletal pain. Collectively, our study suggests that changes in the immunosuppressive repertoire of Tregs can influence the development of a distinct COVID-19 clinical profile, revealing that a possible modulation of Tregs exists among volunteers of the Mild Recovered group between those who did and did not develop certain symptoms, leading to mild disease.